Educación y saberes para la vida: Didácticas innovadoras y creatividad - Simancas Trujillo, Ricardo (Corporación Universitaria Americana, 2018)
The interdisciplinary systemic model of the program allows the integration of different information systems and data capture, triangulated through methodological strategies and investigative pedagogical practices that focus on the information, skills, concepts, attitudes and qualities that students must acquire to be able to address the problems of development and rural life at different levels. It also contributes to the development of the individual's capabilities, namely, learning and development of skills, among which stand out ambivalent communication, the use of ICTs, autonomous learning and teamwork. The Flexible Learning process allows the integration of the dynamic capacities of the communities and the subject, through the implementation of a teaching process based on structured contents that allow a progressive integral development.